1997
DOI: 10.1016/s0092-8674(00)80449-3
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Golgi Structure through Heterotrimeric G Proteins

Abstract: We have previously shown that ilimaquinone (IQ), a marine sponge metabolite, causes complete vesiculation of the Golgi stacks. By reconstituting the IQ-mediated vesiculation of the Golgi apparatus in permeabilized cells, we now demonstrate that this process does not require ARF and coatomers, which are necessary for the formation of Golgi-derived COPI vesicles. We find that IQ-mediated Golgi vesiculation is inhibited by G alpha(s)-GDP and G alpha(i3)-GDP. Interestingly, adding betagamma subunits in the absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
88
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 40 publications
4
88
2
Order By: Relevance
“…Because the morphology of the Golgi is changed upon cholesterol treatment of the cells, these data implicate a function for heterotrimeric G proteins in the maintenance of the Golgi structure as well. This is supported by previous findings showing that possibly free G␤␥ subunits are involved in maintenance of the Golgi structure (74,75). Although the mechanism of G protein-mediated signaling cascades at the Golgi complex is not well understood, our data now suggest that these cascades could be regulated by lipid-enriched microdomains, similar to many other signaling events at the plasma membrane (16).…”
Section: Discussionsupporting
confidence: 91%
“…Because the morphology of the Golgi is changed upon cholesterol treatment of the cells, these data implicate a function for heterotrimeric G proteins in the maintenance of the Golgi structure as well. This is supported by previous findings showing that possibly free G␤␥ subunits are involved in maintenance of the Golgi structure (74,75). Although the mechanism of G protein-mediated signaling cascades at the Golgi complex is not well understood, our data now suggest that these cascades could be regulated by lipid-enriched microdomains, similar to many other signaling events at the plasma membrane (16).…”
Section: Discussionsupporting
confidence: 91%
“…Gilman and colleagues 36 have shown that sequestration of heterotrimeric G protein bg subunits in intact cells strongly inhibits clathrin-coated pit-mediated endocytosis and causes rearrangement of the actin cytoskeleton, and concluded that free bg subunits of G proteins function to permit endocytosis on activation of G protein-coupled receptors. Another line of evidence suggesting the importance of bg subunits of G proteins in vesiculation was shown by Malhotra and colleagues 37,38 . They have shown that ilimaquinone, a marine sponge metabolite, causes complete vesiculation of the Golgi stacks, and later concluded using an elegantly designed reconstitution assay that ilimaquinone-mediated Golgi vesiculation occurs through activation of heterotrimeric G proteins and that it is the free bg subunits and not the activated a subunit that triggers Golgi vesiculation.…”
Section: Discussionmentioning
confidence: 89%
“…All S1P receptors (type [1][2][3][4][5] are classified into a family of G proteincoupled receptors and show distinct expression in tissues and cells, and also show unique G protein-coupling patterns, suggesting distinctive functions 34 . We reasoned that S1P signalling might be involved in the exosomal MVE maturation, because the subunits of G proteins are known to be involved in various types of fission/ fusion events in vesicular trafficking [35][36][37] and protein sorting 38 . In the present studies, we have found that inhibitory G protein (Gi)-coupled S1P receptors on MVEs undergo continuous activation through a constant supply of S1P within the organelles.…”
mentioning
confidence: 99%
“…It has been suggested previously that IQ is able to activate one or more heterotrimeric G-proteins located on the Golgi (25). The activated G-protein dissociates into G␣ and G␤␥ subunits, where the latter remains membrane-associated and causes the fragmentation of the Golgi through downstream mediators.…”
Section: Discussionmentioning
confidence: 99%